ANALISA PENERAPAN ACTIVITY BASED COSTING DIBANDINGKAN DENGAN STANDAR COSTING DALAM PENYUSUNAN ANGGARAN BIAYA KAMAR RAWAT INAP PADA RUMAH SAKIT XYZ - Sukamto, Sukamto; Rimi Gusliana Mais (Bajang Institute, 2025)
This study discusses the problems in preparing the budget for inpatient room costs at XYZ Hospital, which currently still uses standard costing in its calculations. By using the standard costing method, the calculation of the budget is considered to use the same allocation for all inpatient classes, even though each inpatient class has different specifications. This calculation causes the preparation of the budget to be biased and less precise. Because of this condition, the researcher tried to use activity based costing in preparing the budget for inpatient rooms. The purpose of this study is to provide an overview of the benefits of implementing activity based costing in preparing the budget for inpatient rooms. This study uses a qualitative method, using data obtained from XYZ Hospital, analysis and observation and interviews